2021
DOI: 10.1101/2021.03.03.21251639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 antibody magnitude and detectability are driven by disease severity, timing, and assay

Abstract: Serosurveillance studies are critical for estimating SARS-CoV-2 transmission and immunity, but interpretation of results is currently limited by poorly defined variability in the performance of antibody assays to detect seroreactivity over time in individuals with different clinical presentations. We measured longitudinal antibody responses to SARS-CoV-2 in plasma samples from a diverse cohort of 128 individuals over 160 days using 14 binding and neutralization assays. For all assays, we found a consistent and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…We included up to 8 months of follow-up data, in contrast to studies which have been limited to the weeks and months following the initial illness [10,12,27]. Lastly, we have focused on biological specimen collection to facilitate biologically oriented research, which has already begun [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…We included up to 8 months of follow-up data, in contrast to studies which have been limited to the weeks and months following the initial illness [10,12,27]. Lastly, we have focused on biological specimen collection to facilitate biologically oriented research, which has already begun [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have focused on durability of antibodies detected by commercial or lab-developed indirect IgG assays and neutralizing assays, with most studies documenting waning of antibodies following peak reactivity approximately 1 month post-seroconversion. 3,4,5,6,22 Multiple studies have also correlated the waning of binding assay reactivities, and particularly IgG assays with S1, RBD and NC antigens, relative to waning neutralizing antibodies to identify high throughput and low cost assays that could serve as proxies for live virus PRNT or pseudovirus RVPN assays. 13,23 These analyses have demonstrated variable correlations and predictive values of S1, RBD and NC-based immunoassays with waning neutralizing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that ELISA IgG antiNP (Epitopes) is not appropriate for serological evaluation at late time points PSO due to decreased sensitivity. The drop in sensitivity six months PSO is due most likely to the high number of samples from patients with mild form of disease, as it was recently reported [31]. In order to have a better view of the immune status of the COVID-19 convalescent patients, the binding assays should be complemented by sera neutralization assays, which are currently performed for our cohort.…”
Section: Discussionmentioning
confidence: 99%